2003
DOI: 10.1111/j.0105-1873.2003.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch testing with oxidized R‐(+)‐limonene and its hydroperoxide fraction

Abstract: R-(+)-Limonene is an ubiquitous allergen in our environment. It is one of the most widely used fragrance materials not only in fine fragrances but also most often incorporated in domestic and occupational products. Although the non-oxidized R-(+)-limonene itself is not allergenic, it easily forms allergenic products due to autoxidation during handling and storage. 2273 patients at 4 dermatological clinics in Europe were patch tested between 1997 and 1999 in 2 steps. First, the oxidation mixture of R-(+)-limone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 20 publications
11
86
1
1
Order By: Relevance
“…The hydroperoxides of these compounds have been reported to be responsible for the main allergenic effect of turpentine. 21,22) We confirmed that fresh T4 easily reacted with air at room temperature for 30 d to give at least three hydroperoxy derivatives (R f 0.3, 0.5, and 0.69) which were detected as yellow spots by a saturated aqueous KI solution, an indicator of hydroperoxides, on a silica gel TLC plate (EtOAc:hexane, 1:2). These spots, which can also be indicated as characteristic white spots on the TLC image before turning to blue spots on a green-yellow background by a phosphomolybdic acid solution, were detected in an active T4 sample as the -dicarbonyl cleaving agent.…”
Section: Discussion On the Biological Activities Of Monoterpenes And supporting
confidence: 57%
“…The hydroperoxides of these compounds have been reported to be responsible for the main allergenic effect of turpentine. 21,22) We confirmed that fresh T4 easily reacted with air at room temperature for 30 d to give at least three hydroperoxy derivatives (R f 0.3, 0.5, and 0.69) which were detected as yellow spots by a saturated aqueous KI solution, an indicator of hydroperoxides, on a silica gel TLC plate (EtOAc:hexane, 1:2). These spots, which can also be indicated as characteristic white spots on the TLC image before turning to blue spots on a green-yellow background by a phosphomolybdic acid solution, were detected in an active T4 sample as the -dicarbonyl cleaving agent.…”
Section: Discussion On the Biological Activities Of Monoterpenes And supporting
confidence: 57%
“…Although limonene showed a moderate reaction in the GPMT (5), limonene oxide, a secondary allergenic product, due to auto-oxidation (32) (Fig. 2), showed an extreme reaction in the GPMT.…”
Section: Discussionmentioning
confidence: 99%
“…Today, concomitant reactions to gum rosin, Balsam of Peru, and/or fragrances are frequently seen when testing with the baseline series in consecutive patients. A clear correlation is observed between positive patch test reactions to gum rosin and to oxidized fragrance compounds, that is, oxidized limonene and oxidized linalool in consecutive dermatitis patients (Karlberg and Dooms-Goossens 1997;Matura et al 2003Matura et al , 2005. Besides concomitant sensitization, this could be caused by the allergenic hydroperoxides forming nonspecific antigens.…”
Section: Screening and Patch Testingmentioning
confidence: 95%